Persepsi Masyarakat Desa Sumberlesung, Ledokombo, Jember Tentang Makna Kemampuan Menikah dalam Hadits Nabi Muhammad s.a.w. - Ach Dimyati Mustofa (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
Marriage is sunnatullah for the regeneration of Muhammad's people. There are many ways to carry out marriages by the Indonesian people, one of which is that the people of Sumberlesung Village understand the meaning of the ability to marry in the hadith of the Prophet Muhammad, which has implications for the practice of marriage. The perception of the meaning of being able to marry according to the community is first, living, alone, eating alone, thinking alone, second, ajegheh atenah reng seppo dua (maintaining the feelings of mother/father's heart), third, peace of mind, and as a community they say they must have jobs. The social culture is based on ancestors who were strengthened by religious leaders. In this study the authors focus on three aspects of the study; First, what is the perception of the people of Sumberlesung Village, Ledokombo, Jember about the meaning of the ability to marry in the hadith of the Prophet Muhammad. Second, what are the factors that cause the perception of the people of Sumberlesung Village, Ledokombo, Jember about the ability to marry in the hadith of the Prophet Muhammad. Third, what are the implications of the perception of the people of Sumberlesung Village, Ledokombo, Jember.